PENGARUH PENGALAMAN AUDIT, SKEPTISME, INTUISI, DAN INDEPENDENSI AUDITOR TERHADAP KEMAMPUAN AUDITOR MENDETEKSI KECURANGAN - Merta Permana, I Made Bagus Angga; Budiartha, I Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.11.TAHUN.2022DO - 10.24843/EEB.2022.v11.i11.p09, 2022)
This study analyzes the effect of audit experience, auditor skepticism, auditor intuition, and auditor independence on auditor's ability to detect fraud. The sample of this study consisted of 157 auditors from public accounting firm in East Java and Bali. Samples are selected using proportional sampling technique. Data was collected by distributing questionnaires. Data analysis technique used in this research is Structural Equation Modeling (SEM) using Partial Least Square (PLS) software. The results shows that that audit experience, auditor skepticism, auditor intuition, and auditor independence have positive effects on auditor's ability to detect fraud